Finite Element Analysis on Shear Responses of Reinforced Concrete Beams Strengthened with ETS-FRP Bars - Bui, Linh Van Hong; Stitmannaithum, Boonchai (Salehan Institute of Higher Education, 2025)
This study conducts a numerical analysis on the shear performance of reinforced concrete beams retrofitted with fiber-reinforced polymer (FRP) bars with embedded through-section (ETS) technique. The study uses 3D nonlinear finite element method (FEM) and evaluates the shear features of ETS-FRP-strengthened beams in failure modes, shear capacity, stiffness, and ductility. The FE analyses consider the effects of key design parameters, including transverse steel stiffness (Eswρsw), ETS-FRP bar stiffness (Efρf), compressive strength of concrete (f’c), beam geometry, and the values of shear span-to-effective depth (a/d) ratio. Consequently, ETS-strengthened beams with higher concrete strength (f’c) or greater total rigidity of ETS and transverse reinforcement (Efρf + Eswρsw) showed notable improvements in stiffness and load-carrying capacity, with average increases exceeding 20%. The enhancement in shear strength from increased shear reinforcement stiffness is less pronounced in specimens with high concrete strength than in those with lower strength. ETS-strengthened beams with T-shaped sections exhibit more effective performance and safer failure modes. An enhancement in the a/d ratio reduces the stress in ETS bars but results in more ductile failures. This study also proposes a new analytical formulation for determining the maximum shear resistance of ETS-intervened beams, accounting for all failure modes. The model achieved an average predicted-to-tested shear maximum force ratio of 0.93 along with a coefficient of variation of 26%, demonstrating improved accuracy compared to existing models.